Research into Whistleblowing: Protection Against Victimisation - Dussuyer , Inez; Armstrong , Anona; Smith , Russell (Journal of Law and Governance, 2015)
‘Blowing the whistle’ is fraught with risk and this is increasingly recognised by the widespread adoption of whistle-blower legislation to protect the whistle-blower. This paper reviews current legislation, the literature on victimisation of whistle-blowers and reports the results of a study of whistleblowers. Interviews conducted with whistleblowers showed that their experience is usually negative. They become ‘victims’ of a range of harms, including loss of employment, bullying and harassment and emotional distress. The results have implications for the successful operation of the new disclosure laws introduced by the Australian and State governments.